Salem witch trials - Martin, Michael; Bascle, Brian (Mankato, Minn. Capstone Press, 2005)
The story of the 1692 witchcraft trials in Salem, Massachusetts, told in graphic novel format.
Strange behavior in Salem -- Accusations -- The trials -- Witchcraft hysteria -- Did you know?
9 - 12 years
85365
Keywords: Trials (Witchcraft) -- Massachusetts -- Salem -- History -- 17th century; Witchcraft -- Massachusetts -- Salem